THE ROLE OF TRANSFORMATIONAL LEADERSHIP AND FINANCING MANAGEMENT ON THE AVAILABILITY OF SCHOOL INFRASTRUCTURE AND ITS IMPLICATIONS ON THE QUALITY OF EDUCATION IN PUBLIC ELEMENTARY SCHOOL OF PANDEGLANG REGENCY - Alpiah, Alpiah; Rustandi, Tata; Permana, Angrian (International Journal of Multidisciplinary Research and Literature, 2025)
The low quality of education in Indonesia is partly due to the weak role of teachers in exploring students' potential. Teachers often impose their will without considering students' interests and talents, so that their potential does not develop optimally. This study aims to analyze the influence of leadership and financial management on the availability of infrastructure and its implications for the quality of education in public elementary schools in Pandeglang Regency. The study used a quantitative approach with a questionnaire instrument to 105 teachers, and the data were analyzed using Partial Least Square (PLS) through SmartPLS 3.0. The results showed that leadership did not significantly influence the quality of education or infrastructure. In contrast, financial management had a positive and significant effect on the quality of education (t-statistic 2.299; p-value 0.011) and the availability of infrastructure (t-statistic 24.521; p-value 0.000). In addition, the availability of infrastructure was also proven to influence the quality of education (t-statistic 3.032; p-value 0.001). These findings confirm that the quality of education is more influenced by financial management and infrastructure than leadership.